2018
DOI: 10.1093/mnras/sty2448
|View full text |Cite
|
Sign up to set email alerts
|

The observational signatures of supermassive black hole seeds

Abstract: The origin and properties of the initial black hole seeds that grow to produce the observed population of accreting sources remain to be determined. It is a challenge to uniquely disentangle signatures of seeding from fueling and dynamics that shapes the assembly history of growing black holes. To address this, we use a semi-analytic model developed to track the growth of supermassive black holes adopting multiple prescriptions for accretion. In contrast with earlier treatments, we explore the interplay betwee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 161 publications
(146 citation statements)
references
References 103 publications
10
135
1
Order By: Relevance
“…In particular, a recent paper by Dayal et al (2018) used a semi-analytic model to predict high redshift merger rates, and found that for z > 5 mergers, LISA detections of mergers between a DCBH and a stellar mass seed would outnumber the DCBH-DCBH merger detections by two orders of magnitude or more. Furthermore, similar to Ricarte & Natarajan (2018), Dayal et al (2018) found that the merger rate would peak at very low masses, with LISA-detectable mergers (based on SNR > 7) peaking at MBH(1 + z) ∼ 10 4 − 10 5 M , suggesting that the predictions we make for the rate of high-mass DCBH-DCBH mergers represents only a subset of all LISA detections.…”
Section: Black Hole Merger Ratessupporting
confidence: 79%
“…In particular, a recent paper by Dayal et al (2018) used a semi-analytic model to predict high redshift merger rates, and found that for z > 5 mergers, LISA detections of mergers between a DCBH and a stellar mass seed would outnumber the DCBH-DCBH merger detections by two orders of magnitude or more. Furthermore, similar to Ricarte & Natarajan (2018), Dayal et al (2018) found that the merger rate would peak at very low masses, with LISA-detectable mergers (based on SNR > 7) peaking at MBH(1 + z) ∼ 10 4 − 10 5 M , suggesting that the predictions we make for the rate of high-mass DCBH-DCBH mergers represents only a subset of all LISA detections.…”
Section: Black Hole Merger Ratessupporting
confidence: 79%
“…The ability for z = 0 measurements to constrain z > 6 predictions underscores the power of our self-consistent modelling. As shown in Ricarte & Natarajan (2018b), our heavy seeding prescription is consistent with current constraints based on X-ray emission, while the light seeding prescription optimistically assigns almost every low-mass galaxy a MBH seed.…”
Section: Greater Mbh Occupation Fractions?supporting
confidence: 76%
“…The physics of seeding, the abundance of seeds and their initial mass function is one of the key unsolved problems in black hole physics today (see Ricarte & Natarajan 2018b, for a recent detailed discussion). Leveraging the resolution of the Romulus simulations, SMBHs are seeded using recipes based on the local gas properties, rather than simply imposing a halo mass threshold as is often implemented (e.g., Springel et al 2005;Vogelsberger et al 2013;Schaye et al 2015).…”
Section: Smbh Seedingmentioning
confidence: 99%